Software tool for design of three-dimensional positioning systems used in digital manufacturing - León-Medina, Jersson Xavier; Torres-Barahona, Edgar Absalón (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Digital manufacturing creates finished parts from designed models in computer-based manufacturing processes such as CAD-CAM processes, opening the road to flexibility and productivity in industry. This paper presents a software tool that assists the design of digital production equipment, creating complex geometry parts through computerized numerical control. It was started by identifying the characteristics of manufacturing processes capable of automation and it was established a benchmark to define the mechanical, electronic, and control design for three-dimensional positioning equipment.Through a computer tool, the parameters of construction positioning systems were defined, besides, the variables, constants, and criteria were noted, so that by applying theories concerning the electromechanical design, necessary calculations for find the right components belonging to the machine are made. Finally, a user interface allows incorporating data, providing results of the machine design, and getting the structural CAD design of the positioning system.